Philosophy and sociology of modern information activity (modern challenges and scientific and theoretical analysis) - Qizi, Yusifova Gulnare Yusif (Technium Social Sciences Journal, 2022)
Thoughts about the divine origin of information resurfaced in the 21st century and were called the information age. The views of ancient and medieval thinkers on information are more like mystical and romantic interpretations. Scientists of the twentieth century tried to interpret information more fully by materializing it. Thus, the study of information technology, information and communication technologies and their intensive application in our daily lives have made this area extremely relevant. Sometimes it is difficult for experts who ask "what’s going on" to understand the nature of global information. In ancient times, the process of social communication and exchange of information was not studied by classical historians, or rather, was not in the center of attention. At the beginning of civilization, various questions of people about nature and man, in addition to everyday needs, were discussed in interaction, and in the absence of science, "words and interpretation" formed the basis of communication. The people who proclaimed and interpreted the divine source of the Word became "wise" and soon began to distinguish themselves from others, claiming their superiority. Thus, priests, priests, preachers, monks and dervishes were formed as carriers of divine wisdom. It is important to take a closer look at the object as part of a philosophical review of the theories put forward about the definition of information and its configuration. This article can be considered a step in that direction.